Mainlobe beamwidth maximization for wide-beam array antenna with desired minimum power gain constraint. Issue 3 (11th February 2022) - Lei, Shiwen; Hu, Haoquan; Chen, Bo; Tian, Jing; He, Ziyuan; Tang, Pu; Qiu, Xiangdong
Abstract : In this paper, the problem of maximizing the beamwidth with array antenna giving the desired minimum power gain in the wide-beam mainlobe is addressed. Termed this problem as Mainlobe BeamWidth Maximization (MBWM). This paper, by optimizing the gain pattern instead of optimizing the beam pattern, first sets up the mathematical model for the MBWM problem. It comes out that the MBWM problem is non-convex, hence cannot be solved effectively in polynomial time. To simplify the solving processes, the MBWM problem, thereafter, is converted into a series of power gain pattern synthesis (PGPS) problems. The bisection strategy together with the processing procedures for the PGPS problem are utilized to design an iterative algorithm to solve the MBWM problem. Numerical simulations compared with the existing methods which optimize the beam pattern are carried out.